The transcription factor CmLEC1 positively regulates the seed-setting rate in hybridization breeding of chrysanthemum. (10th August 2021) - Xu, Sujuan; Wu, Ze; Hou, Huizhong; Zhao, Jingya; Zhang, Fengjiao; Teng, Renda; Ding, Liping; Chen, Fadi; Teng, Nianjun
Abstract: Distant hybridization is widely used to develop crop cultivars, whereas the hybridization process of embryo abortion often severely reduces the sought-after breeding effect. The LEAFY COTYLEDON1 ( LEC1 ) gene has been extensively investigated as a central regulator of seed development, but it is far less studied in crop hybridization breeding. Here we investigated the function and regulation mechanism of CmLEC1 from Chrysanthemum morifolium during its seed development in chrysanthemum hybridization. CmLEC1 encodes a nucleic protein and is specifically expressed in embryos. CmLEC1 's overexpression significantly promoted the seed-setting rate of the cross, while the rate was significantly decreased in the amiR- CmLEC1 transgenic chrysanthemum. The RNA-Seq analysis of the developing hybrid embryos revealed that regulatory genes involved in seed development, namely, CmLEA (late embryogenesis abundant protein), CmOLE (oleosin), CmSSP (seed storage protein), and CmEM (embryonic protein), were upregulated in the OE (overexpressing) lines but downregulated in the amiR lines vs. wild-type lines. Future analysis demonstrated that CmLEC1 directly activated CmLEA expression and interacted with CmC3H, and this CmLEC1–CmC3H interaction could enhance the transactivation ability of CmLEC1 for the expression of CmLEA . Further, CmLEC1 was able to induce several other key genes related to embryo development. Taken together, our results show that CmLEC1 plays a positive role in the hybrid embryo development of chrysanthemum plants, which might involve activating CmLEA 's expression and interacting with CmC3H. This may be a new pathway in the LEC1 regulatory network to promote seed development, one perhaps leading to a novel strategy to not only overcome embryo abortion during crop breeding but also increase the seed yield.